2021
DOI: 10.1186/s42238-021-00099-5
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cannabis use and IVF outcome—a cohort study

Abstract: Background The effects of cannabis use on male and female reproduction have been the focus of scientific research for decades. Although initial studies raised concerns, more recent studies were reassuring. Considering the recent legalization of recreational use of cannabis in Canada, we sought to analyze IVF outcomes among users and non-users in a single IVF center. Methods This is a retrospective cohort study from a single IVF center assessing IVF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Given that blastocysts generated from sperm exposed to all concentrations of THC had fewer ICM cells, and that ICM quality is highly predictive of pregnancy and implantation rates [ 137 ], paternal cannabis use would be expected to adversely affect IVF outcomes. However, current clinical research shows no associations between paternal cannabis use and implantation rates or time to pregnancy [ 24 , 25 ]. In support of our results regarding cleavage and blastocyst rates, Har-Gil et al, (2021) observed no differences in blastocyst formation rates between cannabis users and non-users seeking infertility treatment [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that blastocysts generated from sperm exposed to all concentrations of THC had fewer ICM cells, and that ICM quality is highly predictive of pregnancy and implantation rates [ 137 ], paternal cannabis use would be expected to adversely affect IVF outcomes. However, current clinical research shows no associations between paternal cannabis use and implantation rates or time to pregnancy [ 24 , 25 ]. In support of our results regarding cleavage and blastocyst rates, Har-Gil et al, (2021) observed no differences in blastocyst formation rates between cannabis users and non-users seeking infertility treatment [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, current clinical research shows no associations between paternal cannabis use and implantation rates or time to pregnancy [ 24 , 25 ]. In support of our results regarding cleavage and blastocyst rates, Har-Gil et al, (2021) observed no differences in blastocyst formation rates between cannabis users and non-users seeking infertility treatment [ 25 ]. In contrast to our findings, the same researchers also found no effect of paternal cannabis use on blastocyst quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past two decades there has been several studies that have evaluated the impact of illicit drug use on IVF and pregnancy outcomes (20)(21)(22). However, there are some limitations regarding the investigation of illicit drug use on reproductive function due to the ethical concerns of administration, and patient underreporting (23).…”
Section: The Impact Of Illicit Drug Use On Ivf Outcomesmentioning
confidence: 99%